Forests over limestone in Guiuan, Eastern Samar, the Philippines: Species composition and influencing environmental factors - INOCENCIO E. BUOT JR.; ELAINE LOREEN C. VILLANUEVA; MARNE G. ORIGENES; REN DIVIEN R. OBEÑA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Buot Jr IE, Villanueva ELC, Origenes MG, Obeña RDR. 2023.  Forests over limestone in Guiuan, Eastern Samar, the Philippines: Species composition and influencing environmental factors. Biodiversitas 24: 5123-5136. Forests over limestone are critical ecosystems providing numerous ecosystem services. However, the ecology of these ecosystems is less studied like the Guiuan Marine Resource Protected Landscape and Seascape (GMRPLS) in Eastern Samar, Philippines which incidentally is affected by strong typhoons. Studies on forests over limestone are even more essential to understand the vegetation ecology providing insights in crafting appropriate management strategy to sustain ecosystem services. Hence, the study aims to identify the woody vegetation diversity and composition of forests over limestone in GMRPLS, and to analyze the environmental factors influencing the physiognomy and ecology of the forests. Standard vegetation techniques were used and a total of nine plots with size of  20 × 20m each were established to assess the tree species (?1m height). Plant abundance data were recorded and computed. Soil samples were collected while climate data were obtained from the Guiuan, Eastern Samar Weather Station. Cluster analysis using relative density of trees per plot was done in order to identify major plant communities. Subsequently, a canonical correspondence analysis was carried out to pinpoint which environmental variables influenced the plant data set. Results show a total of 37 species belonging to 17 families, with 18 species are listed under by IUCN and seven species are listed by DAO 2017-11. Cluster analysis indicated 3 vegetation groupings or clusters named after the dominant species per plot, namely Cluster I (Hancea-Calophyllum-Macaranga-Ficus-Gnetum), Cluster II (Monoon-Wallaceodendron-Artocarpus-Hancea-Bago-eho), and Cluster III (Bridelia-Monoon-Neonauclea-Gnetum-Artocarpus-Sterculia-Hancea). GUI 02 plot (Cluster 1) was observed as the most diverse with the highest Simpson’s index and Fisher’s alpha, as well as the highest in total number of tree species. Canonical correspondence analysis indicated elevation, temperature and anthropogenic disturbances as the major factors influencing the vegetation diversity and composition. This can be used to formulate forest management strategies for the sustainable conservation of forests over limestone in GMRPLS.